Development of Gymnastics Learning Media based Android - Fegie Rizkia Mulyana; Ridwan Gumilar; Novi Soraya (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2022)
This study aims to develop and produce products in the form of gymnastics learning media based on android applications. This study uses research and development research methods with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluations). The research carried out only reached the development or development stage, because this research only developed and produced an android application-based gymnastics learning media product called "GYMBASTECH" (Gymnastics Basic Techniques). The validation of this gymnastics learning media was carried out by three experts, namely floor exercise material experts, physical education learning media experts, and technical and informatics experts. The instruments used in this study were guidelines from interviews, questionnaires or validation questionnaires for 3 experts, and the system usability scale (SUS) to determine the usefulness of the media determined by the user as a product user. The result of the product obtained is that the percentage of floor exercise material experts is 80.77%, physical education learning media experts are 81.25%, and technical and informatics experts are 80.77%. From the results of the three expert validations obtained an average of 82.51% this indicates that the gymnastics learning media "GYMBASTECH" is categorized as good and feasible to use in the learning process. The results of the response to the use of the gymnastics learning media product "GYMBASTECH" obtained an average of 58.44%, so this product is categorized as good. Based on the results of the three experts, and the product usability test using the system usability scale, the product in the form of gymnastics learning media "GYMBASTECH" is said to be feasible and can be used in the gymnastics learning process. The next research plan will test the effectiveness of the product so that it can be seen the effect of "GYMBASTECH" media when used in the gymnastics learning process.